Parametric modeling of sports prostheses based on the flat spring design formulas - Hase, K.; Togawa, H.; Kobayashi, S.; Obinata, G. (Journal of Biomechanical Science and Engineering, 2020)
Sports prosthesis for lower-extremity amputees has a mechanical structure similar to flat springs, and its elastic energy is expected to improve sports performance. However, it is quite challenging to represent the mechanical phenomena during the takeoff action with sports prosthesis because the contact point to the ground moves based on the direction and deformation of the prosthesis. The purpose of this study is to propose a parametric model of sports prosthesis based on the flat spring design formulas to represent the deformation and rolling contact with the ground with a reasonable computational cost. The shape of the prosthesis is modeled as serial elements, and it can easily be changed by using design parameters, such as the curvature and length of each element. The curvature of each element of the prosthesis is modified by the deflection angle of the flat spring model, and the contact point to the ground is calculated by considering the deformation and rolling contact. The spring properties obtained from the proposed model well agreed with the result of a finite element analysis. Moreover, simulation results revealed that the deformed shape of the prosthesis and the takeoff action in the long jump qualitatively agreed with the actual phenomena. As future research, the proposed model, coupled with the human body model, will be applied to a computer simulation system to optimize the shape of the prosthesis in order to improve sports performance.